OPPORTUNITIES FOR SSW NO.2 RESIDENCY STATUS: A CASE STUDY OF CHINESE MIGRANT WORKERS IN JAPAN - Nur Raudha, Sabrina; Iskandar, Kurniawaty (WILAYAH: The International Journal of East Asian Studies, 2024)
Approaching five years since the issuance of unlimited residency status for foreign workers in the 3K job sector, the acquisition of Specified Skilled Worker (SSW) No.2 status in Japan remains considerably below the government’s anticipated target. This research aims to analyze the opportunities of SSW No.2 residency status for foreign workers, focusing on the case study of Chinese migrant workers from the dual labor market theory perspective. The research employs a qualitative approach with data collection conducted through literature sources. The findings reveal that, thus far, SSW No.2 status is predominantly held by Chinese migrant workers. However, the opportunities for foreign workers to obtain this status are notably limited due to a complex and challenging acquisition process. Employment in the secondary market accompanying this status requires foreign workers with skills equivalent to local workers. Aside from the benefit of bringing one’s family, this status seems to offer no other long-term appeal. An urgent reevaluation of the procedures for obtaining SSW No.2 status is deemed necessary as a long-term solution to address the labor crisis in Japan.